Factors Predicting Recurrence of Clostridium difficile Infection (CDI) in Hospitalized Patients: Retrospective Study of More Than 2000 Patients. Issue 5 (June 2015) - Abdelfatah, Mohamed; Nayfe, Rabih; Nijim, Ala; Enriquez, Kathleen; Ali, Eslam; Watkins, Richard R.; Kandil, Hossam
Abstract : Background: Clostridium difficile infection (CDI) has increased in incidence and severity worldwide, causing direct costs estimated to range from US 3.2 billion to 4.8 billion. The aim of this study was to investigate and identify factors that predict recurrence of CDI. Methods: This was a retrospective case-control study between 2007 and 2013 on patients admitted with CDI. Recurrent CDI is defined as a new episode of diarrhea within 90 days confirmed by a positive stool C. difficile toxin assay or polymerase chain reaction, after resolution of the initial CDI episode for at least 10 days and after discontinuation of the CDI therapy. Results: Three thousand twenty patients were diagnosed with CDI between January 2007 and December 2013. Two hundred nine of 2019 patients in the study had a recurrence of CDI within 90 days of the end of the initial CDI episode (10.3%). Multivariate analysis showed that most of the recurrences occurred in patients with comorbidities, particularly chronic kidney disease (odds ratio, 1.3; 95% confidence interval [CI], 1.0–2.4; P = 0.039). In addition, a higher percentage of patients in the recurrence group were prescribed proton-pump inhibitors (odds ratio, 1.65; 95% CI, 1.0–1.7; P = 0.002) and steroids (odds ratio, 1.65; 95% CI, 1.0–1.5; P = 0.047). Conclusions: Our data suggest that the use of glucocorticoids, use of proton-pump inhibitors, and having end-stage renal disease are significant risk factors associated with recurrent CDI.